Il prestito verbale nel contatto italiano-tedesco (Atti del Sodalizio Glottologico Milanese, 2014)
The topic of this paper is lexical borrowing and in particular borrowing and adaptation processes that involve verbs. Within the framework of loanword typology, the four verbal borrowing strategies introduced by [Wohlgemuth 2009] will be first described and then further discussed with data derived from German dialects spoken in Italy. It will be shown that working both within dialectology and with freely occurring speech data (besides standard languages and lexicographic sources) enlarges the variety of borrowing strategies also when very similar language pairs are involved. KEYWORDS: lexical borrowing, verbs, multilingualism, Italian, German